Effects of indomethacin on prostanoid synthesis and vasomotor responsiveness in endothelium-denuded abdominal and thoracic aortas of Wistar rats - Ruth M. López; Janette E. López; Jorge S. López; María C. Castillo; Gustavo Guevara; José A. Morales; Oscar A. López; Jair Lozano; Enrique F. Castillo (Clinical and Experimental Hypertension, 2017)
In endothelium-denuded abdominal (but not thoracic) aortas of rats, the nonselective cyclooxygenase (COX) inhibitor, indomethacin, suppressed contractions evoked by α-adrenergic agonists hypothetically mediated by prostanoids. We aimed to identify these non-endothelial-derived contractile prostanoids released by α-adrenergic receptors activation. Endothelium-denuded abdominal and thoracic aortas of Wistar rats were used for biochemical and functional analyses. Western blot analysis showed that COX-1 and COX-2 protein levels were respectively equivalent in endothelium-denuded abdominal and thoracic aortas. Enzyme immunoassay data supported direct evidence of phenylephrine-stimulated release of prostanoids (PGI2, PGE2, and PGF2α) by thoracic and abdominal aortas without endothelium, and their almost complete inhibition by 1 μM indomethacin. Isometric force measurements established that 10 μM indomethacin—but no lower concentrations—inhibited the contractions evoked by phenylephrine in endothelium-denuded abdominal aorta. In this preparation, 10 μM indomethacin also depressed the contractions provoked by angiotensin II and high K+ (80 mM). In fact, indomethacin (up to 1 mM) caused concentration-dependent reductions in all abovementioned contractile responses. In endothelium-denuded thoracic aortas, however, only 1 mM indomethacin significantly depressed the contractile activity stimulated by either phenylephrine, angiotensin II, or high K+. Hence, there was a clear quantitative difference in response to indomethacin between abdominal and thoracic aortas without endothelium. Altogether, the results indicate that prostanoids induced by phenylephrine in abdominal and thoracic aortas were derived from non-endothelial COX-mediated metabolism; notably, the decrease in prostanoid synthesis could not account for the inhibition of vasoconstrictor responses by indomethacin: Through COX-independent actions, indomethacin inhibited aortic smooth muscle contractility.